Is it time to reconsider how to manage oocytes affected by smooth endoplasmic reticulum aggregates?. Issue 4 (26th February 2019) - Ferreux, Lucile; Sallem, Amira; Chargui, Ahmed; Gille, Anne-Sophie; Bourdon, Mathilde; Maignien, Chloé; Santulli, Pietro; Wolf, Jean Philippe; Patrat, Catherine; Pocate-Cheriet, Khaled
Abstract: STUDY QUESTION: Did the revised Alpha/ESHRE consensus (Vienna, 2017) bring a real answer on managing oocytes with aggregates of smooth endoplasmic reticulum (SERa)? SUMMARY ANSWER: According to the currently available literature, a case by case approach on the time of injecting/inseminating SERa+ oocytes may be not helpful for embryologists making a decision, so we suggest fertilizing both SERa+ and SERa− oocytes and prioritizing embryos derived from SERa− oocytes. WHAT IS KNOWN ALREADY?: In 2011, the Istanbul consensus recommended not to inject/inseminate SER+ oocytes due to adverse foetal outcomes reported in literature. At the end of 2017, a panel of experts reconsidered this recommendation and advised a case by case approach. Hence, with a lack of clear recommendations, in-vitro fertilization practitioners still have heterogeneous attitudes when managing SERa+ oocytes. In this context of controversy, an updated review could be helpful in (i) forming a common language for managing cases of SERa+ oocytes and (ii) offering the most ethical practice and best care for patients seeking infertility treatment or fertility preservation. STUDY DESIGN, SIZE, DURATION: This review (with a last literature search on 1 June 2018) evaluated the effect of the SER dysmorphism on embryological and neonatal outcomes. PARTICIPANTS/MATERIALS, SETTING, METHODS: Studies were considered for inclusion if they were prospective or retrospective cohort or case–control studies. Electronic searches of the Pubmed and Embase databases were done using the keyword combination: smooth endoplasmic reticulum, SER, oocyte and zygote. Abstracts and articles written in English and limited to humans were included. MAIN RESULTS AND THE ROLE OF CHANCE: The search returned a total of 726 studies among which 21 met the inclusion criteria. The literature does not unanimously support a negative association between SERa and embryogenesis, implantation or assisted reproductive therapy outcomes. The reviewed studies reported 112 neonatal outcomes after transfers where at least one embryo originated from oocyte affected by SERa. They included 101 healthy babies, three live births with malformations, three neonatal deaths, one stillbirth and four medical interruptions of pregnancy. After transfer of embryos exclusively derived from SERa+ oocytes, a total of 48 healthy newborns were reported along with four babies with perinatal complications (including one ventricular septal defect), one stillbirth, one neonatal death and one pregnancy termination for multiple malformations. LIMITATIONS, REASONS FOR CAUTION: As with any review, this review was limited by the quality of the included studies especially in terms of possible methodological limitations, the limited sample size and the retrospective aspect of the studies. Among the 21 selected studies, seven were abstracts and two were case reports. Of the remaining 14 studies, only three were prospective. The tools used in identifying SERa+ oocytes may have varied from one study to another and a consequent misclassification cannot be excluded. Considering the poor resolution of light microscopy in detecting SER aggregates, we are not sure that apparently SERa− oocytes do not really exhibit such a dysmorphism if they were analysed under electronic microscopy or a time lapse system. WIDER IMPLICATIONS OF THE FINDINGS: In the light of the existing data and the lack of a real link between fertilizing SERa+ oocytes and the occurrence of embryo aneuploidy/malformations, we think that discarding SERa+ oocytes may be not the most ethical approach even in patients with large cohorts on the day of oocyte retrieval. Avoiding the wastage of oocytes and embryos with respect to medical ethics remains a constant concern in daily IVF practice. Thus, we recommend that all mature oocytes could be fertilized and embryos originating from SERa− oocytes would be preferably transferred, even if they come from a cohort with SERa+ oocytes. The remaining embryos derived from SERa+ oocytes could be considered with a lower priority for transfer after obtaining consent from the couple if a strict follow-up of the pregnancy and the baby is performed. STUDY FUNDING/COMPETING INTEREST(S): We have no conflict of interest to declare and no funding was received. REGISTRATION NUMBER: N/A.